The impact of emojis on perceived responsiveness and relationship satisfaction in text messaging - Eun Huh (PLoS ONE, 2025)
Partner responsiveness is a key predictor of likability and overall relationship quality, yet its role in digital communication remains insufficiently studied. This study examined how the inclusion of emojis in text messages influences perceptions of responsiveness and, subsequently, likability, closeness, and relationship satisfaction. A sample of 260 participants viewed 15 text-based conversations in which they assumed that they received responses from their friends. Participants were randomly assigned to one of two conditions (e.g., text-only responses or responses that combined text and emojis) for each conversation. Perceptions of responsiveness, likability, closeness, and relationship satisfaction were assessed using pre-established Likert scales. The results showed that messages containing emojis were perceived as more responsive than text-only messages. Perceived responsiveness, in turn, significantly predicted higher ratings of closeness and relationship satisfaction. These findings demonstrate that the influence of partner responsiveness, enhanced through the use of emojis, extends beyond face-to-face interactions into digital interactions. They highlight the critical role of perceived responsiveness in digital contexts and suggest that emojis can enhance relationship satisfaction by acting as nonverbal cues that complement or substitute face-to-face communication.